2017
DOI: 10.1097/tp.0000000000001375
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus in Living Pancreas Donors

Abstract: Background Living donor pancreas transplant is a potential treatment for diabetic patients with end-organ complications. While early surgical risks of donation have been reported, long-term medical outcomes in living pancreas donors are not known. Methods We integrated national Scientific Registry of Transplant Recipients data (1987–2015) with records from a nationwide pharmacy claims warehouse (2005–2015) to examine prescriptions for diabetic medications and supplies as a measure of post-donation diabetes m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…2327 Data on long-term outcomes are limited, but a recent study of 45 living pancreas donors that included 69% simultaneous kidney donations found that over a mean postdonation follow-up period of 16.3 years, 26.7% filled prescriptions for diabetes treatments, compared with 5.9% of kidney-alone living donors (odds ratio 4.13, 95% confidence interval 1.91–8.93; P = 0.0003). 28 These findings suggest a more than 4-fold increase in the incidence of diabetes following living kidney-pancreas donation, a concern that warrants longer follow-up and investigation to adequately understand risks to the donor.…”
Section: Discussionmentioning
confidence: 93%
“…2327 Data on long-term outcomes are limited, but a recent study of 45 living pancreas donors that included 69% simultaneous kidney donations found that over a mean postdonation follow-up period of 16.3 years, 26.7% filled prescriptions for diabetes treatments, compared with 5.9% of kidney-alone living donors (odds ratio 4.13, 95% confidence interval 1.91–8.93; P = 0.0003). 28 These findings suggest a more than 4-fold increase in the incidence of diabetes following living kidney-pancreas donation, a concern that warrants longer follow-up and investigation to adequately understand risks to the donor.…”
Section: Discussionmentioning
confidence: 93%
“…However, the link between beta-cell mass and beta-cell function has been previously established in several studies in healthy living donors who had undergone hemipancreatectomy [ 28 30 ], all of them reporting a deterioration of insulin secretion and glucose tolerance in these subjects. This model is particularly relevant since individuals undergoing hemipancreatectomy exhibit a significant decrease in beta cell mass while beta-cell area to total pancreatic tissue ratio is conserved.…”
Section: Discussionmentioning
confidence: 99%